2018
DOI: 10.1590/s1677-5538.ibju.2017.0525
|View full text |Cite
|
Sign up to set email alerts
|

Polygamy, sexual behavior in a population under risk for prostate cancer diagnostic: an observational study from the Black Sea Region in Turkey

Abstract: Aim:Although prostate cancer (PCa) is the most common cancer type in men, a replaceable risk factor has not yet been established. In our study, we assessed the relationship between the number of sexual partners, age of first sexual experience and age of first masturbation and prostate cancer incidence.Materials and Methods:In Ordu University Department of Urology between January 2013 and September 2016, in PSA elevation and rectal examination, patients with prostate biopsy were evaluated due to nodule palpatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 14 publications
1
8
0
Order By: Relevance
“…Cirakoglu A et. al (16) assessed the correlation between the number of sexual partners, monthly frequency of sexual relations, age of first sexual debut, and age of first masturbation with the incidence of prostate cancer. They concluded that there might be an association between the number of sexual partners and prostate cancer in the patient group with PSA levels above 4ng/ml.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cirakoglu A et. al (16) assessed the correlation between the number of sexual partners, monthly frequency of sexual relations, age of first sexual debut, and age of first masturbation with the incidence of prostate cancer. They concluded that there might be an association between the number of sexual partners and prostate cancer in the patient group with PSA levels above 4ng/ml.…”
Section: Discussionmentioning
confidence: 99%
“…They concluded that there might be an association between the number of sexual partners and prostate cancer in the patient group with PSA levels above 4ng/ml. Thus, suggested avoidance of sexual promiscuity or participation in protected sex to be beneficial measures to protect against prostate cancer (16).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported the impact of sociocultural factors on risk behaviors and sexual behaviors in different communities [5, 1012]. A study on culture and sexual behaviors among Iranian and New Zealand women found that sexual behaviors and sexual desire and pleasure were related to community culture, beliefs and past experiences regarding sexual activities [44].…”
Section: Discussionmentioning
confidence: 99%
“…Some communities widely accept sexual-related behaviors in public areas, while others condemn this behavior [11]. Some communities accept polygamy, while others do not [12]. Sex workers are legal and allowed in some countries, whereas they are not allowed in others [13, 14].…”
Section: Introductionmentioning
confidence: 99%
“…I read the article by abdullah cirakoglu et al (1) with great interest but i have some points of concern with this article.…”
mentioning
confidence: 99%